The encroachment framework 1 - van der Rhee, Bo; Schmidt, Glen (Henry Stewart Talks, 2014)
New products can take market share, New attributes can be introduced, The encroachment framework, Six types of new products & services, Immediate high-end, Immediate low-end, New attribute high-end, Fringe market low-end, Detached market low-end, New market high-end, Core attribute performance vs. New attribute performance